Artemisinin synergizes with CCCP in autophagic cell death induction via ER stress in uveal melanoma - Minyue Xie; Xiang Gu; Zheng Zhao; Yu Hua; Qianru Wu; Yizhen Tang; Ai Zhuang; Shengfang Ge; Renbing Jia; Jie Yu; Jing Ruan; Xianqun Fan (iScience)
Summary: Uveal melanoma (UM) is the most common primary intraocular malignancy in adults, and it is associated with a poor prognosis due to the lack of effective targeted therapies. Artemisinin (ARS), a widely used antimalarial drug, has demonstrated anti-tumor effects in several types of cancer, including UM. However, these effects are primarily observed at high concentrations, which restricts its broader use. Our study reveals mitochondrial uncoupler agents as synergistic partners with DHA in treating UM, both in vitro and in vivo. Specifically, the combination of DHA and CCCP, a representative mitochondrial uncoupler, induced endoplasmic reticulum (ER) stress by enhancing the binding of ATF4 and CHOP to the SESN2 promoter region. This ER stress subsequently activated autophagic cell death, augmenting UM cell eradication. Our findings suggest that combining DHA with mitochondrial protonophore uncouplers inhibits UM proliferation, underscoring the therapeutic promise of this approach for UM treatment.